Exploration of Friction Material on Weaving Crafts in Sukarara Village, Central Lombok, NTB - Osi, Zaena Sultona; Maharani, Bintang; Martiana, Rina; Purnama, Dunia; Mahrus, Mahrus; Andayani, Yayuk (Indonesian Journal of Innovation in Education Research, 2025)
This study aims to determine and explore the relationship between friction and weaving crafts in Sukarara Village, Central Lombok, NTB. Ecotourism is the main focus, especially on weaving crafts in the Sasak tribe as an attraction for tourists. The delivery process carried out manually by the community involves interaction between yarn and looms, where friction plays an important role in the quality of the fabric produced. Through a qualitative approach, data were obtained from interviews with weavers and local communities, as well as direct observation. The results of the study indicate that the community's understanding of the principles of physics, especially friction, is manifested in their telling practices. Various factors, including yarn type, ordering technique, and weaver skills, affect friction and fabric quality. This study links traditional knowledge with scientific concepts, providing new insights into the application of physics in everyday life and the importance of preserving local culture